2022
DOI: 10.1007/s11686-022-00635-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potency of Ginger, Garlic, and Pomegranate Extracts Against Cryptosporidium parvum-Mediated Gastro-Splenic Damage in Mice

Abstract: Purpose Cryptosporidium parvum is a protozoan parasite infecting most mammalian hosts and causing major health issues. The present study investigated the efficacy of ginger (Zingiber officinale), garlic (Allium sativum), and pomegranate (Punica granatum) peel extracts on the development and progression of experimental cryptosporidiosis in mice. Methods Eighty-two mice were assigned to 6 groups: control, infected non-treated, metronidazole (MTZ), ginger, ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Intestinal sections of AS‐treated mice showed a reduction in the number of Cryptosporidium oocysts, as well as submucosal mild edema and capillary congestion. Similarly, El‐Shewehy et al (2022) reported a few Cryptosporidium oocysts with mild degenerative lesions of the gastric lining epithelial cells after treatment with garlic extract. Contrarily, Gaafar (2012) and Abouel‐Nour et al (2016) found that treating infected mice with garlic led to the complete eradication of Cryptosporidium oocysts from their feces and intestinal sections.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Intestinal sections of AS‐treated mice showed a reduction in the number of Cryptosporidium oocysts, as well as submucosal mild edema and capillary congestion. Similarly, El‐Shewehy et al (2022) reported a few Cryptosporidium oocysts with mild degenerative lesions of the gastric lining epithelial cells after treatment with garlic extract. Contrarily, Gaafar (2012) and Abouel‐Nour et al (2016) found that treating infected mice with garlic led to the complete eradication of Cryptosporidium oocysts from their feces and intestinal sections.…”
Section: Discussionmentioning
confidence: 89%
“…Several attempts were made to evaluate plant and medicinal herb extracts for the treatment and prevention of cryptosporidosis in vivo and in vitro, including the use of curcumin (Asadpour et al, 2018), olive ethanolic extract (Teichmann et al, 2016), Citrus sinensis peel extract (Abd El Wahab et al, 2022), and Herniaria hemistemon aerial extract (Ghareeb et al, 2023). Additionally, a number of investigates have been carried out to evaluate the impact of A. sativum extracts on cryptosporidiosis (Abouel‐Nour et al, 2016; EL‐Shewehy et al, 2022; Farid et al, 2022). However, according to the available literature, green ZnO‐NPs have not been used in any previous studies for the treatment of cryptosporidiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Garlic and turmeric extracts exhibited the highest inhibitory effect in relation to the ST3 viability. The garlic activity was also observed with other protozoan parasites, such as Giardia lamblia [ 66 , 67 ], Cryptosporidium parvum [ 68 ], and Entamoeba histolytica [ 23 ] . According to the literature, Blastocystis ST7 has been shown to be more resistant to anti-parasitic drugs [ 69 , 70 ] and against the host innate immune response [ 71 ] compared to ST1 and ST4 isolates.…”
Section: Discussionmentioning
confidence: 99%